Educator Perceptions of DevOps Teaching Recommendations and Their Alignment with Common Challenges - Fernandes, Marcelo; Paiva, Pablo; Ferino, Samuel; Coelho, Roberta; Aranha, Eduardo; Kulesza, Uirá; Treude, Christoph (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2025)
DevOps education presents unique pedagogical challenges due to the diversity of tools, rapid technological change, and the multidisciplinary nature of the field. Although previous work has proposed recommendations to address these challenges, it is unclear how educators perceive these recommendations and whether they align with the challenges encountered in practice. In this paper, we present a quantitative and qualitative methods study involving 11 DevOps educators who interacted with Improve, a tool that presents a curated set of educational challenges and recommendations derived from previous literature. Educators indicated which recommendations they already use, which they intend to use, and which challenges they experience and are motivated to address. Our findings show that 22.6% of the recommendations were new to educators and considered potentially useful, while 59.2% were already in use. Additionally, 66.3% of the challenges were considered relevant, with most of them having linked recommendations that educators were already using or willing to adopt. This study provides empirical insights into the perceived usefulness of existing recommendations, identifies gaps in challenge-recommendation mappings, and supports future efforts to design and disseminate more targeted educational guidance for DevOps teaching.